Biochemistry - Zubay, Geoffrey L. (Dubuque,IA, Wm C Brown Publishers, 1998)
A comprehensive biochemistry textbook, this fourth edition has been fully revised and up dated presenting a discussion of each class of structures followed by its metabolism.
Includes bibliographical references; Appendix A-B, A1-A55; Glossary G1-G11; Index I1-I28
Keywords: Biochemistry